Preparation of injectable hydrogels from temperature and pH responsive grafted chitosan with tuned gelation temperature suitable for tumor acidic environment - Natnicha Jommanee (2018)
© 2018 Elsevier Ltd In this present work, stimuli responsive polymers that can respond to the temperature and pH of the environment were prepared. A series of temperature responsive diblock copolymers based on poly(ethylene glycol) methyl ether (mPEG) and ε-caprolactone (CL) were synthesized. Subsequently, the diblock copolymers were grafted onto chitosan, a pH responsive biopolymer. These chitosan-graft-(mPEG-block-PCL) (chitosan-g-(mPEG-b-PCL)) graft copolymers were structurally characterized by1H NMR and FTIR and their sol-gel phase transitions were analyzed by the test tube inversion method as well as dynamic rheological measurements. These chitosan-g-(mPEG-b-PCL) graft copolymers demonstrated tunable temperature and pH responsive sol-gel phase transitions that correspond well with body temperature and pH of acidic tumor microenvironments. Gelation temperature (Tgel) decreased with increasing pH of the system, increasing PCL composition in the diblock copolymers, increasing solution concentration and decreasing grafting content of the diblock copolymers on chitosan. The graft copolymer hydrogels successfully showed the sustained release of both doxorubicin and curcumin for up to 2 weeks. The designed system was based on chitosan-g-(mPEG-b-PCL) graft copolymers, of which chitosan showed pH responsive properties and mPEG-b-PCL acted as a temperature sensitive moiety. In addition, mPEG and PCL are recognized as biocompatible polymers and chitosan has been engaged in various pharmaceutical research. Thus, this system could be considered an alternative choice for drug delivery applications.